Penerapan Metoda Deep Fat Frying Dan Rekayasa Proses Melalui Pemanfaatan Enzim Protease Untuk Perbaikan Karakteristik Produk Gorengan - Indarto, Cahyo; Burhan, Burhan; Maflahah, Iffan; Farida Asfan, Dian; Mojiono, Mojiono; Firmansyah, Arief (Jurnal Ilmiah Pangabdhi, 2024)
Fried foods are prevalent among the public. This type of food is very cheap and can be enjoyed in a relaxed atmosphere. Other things about fried food include that it is practical in serving and can overcome hunger in a person's limited time. Fried foods are also a practical snack to serve to guests. Fried foods are generally fried using the panfrying method with sufficient oil. The result of the frying process using this method is that the level of cooking is uneven, resulting in less crispy and longer frying time. People generally use baking soda to get crispier products. Excessive use of baking soda harms health and can cause a bitter taste in fried products. This study offers a solution to overcome this problem. The study provides a solution in the form of technology: the deep fat frying method and the use of protease enzymes to improve the character of the fried food produced – application of this technology through service in a case study (Gumulan village, Jombang). Introducing this technology results in fried products (meat, shrimp, and tofu) with superior characteristics: tasty, crunchy, and attractive. By introducing this technology, it is hoped that the target community can apply it to produce products that have superior characteristics. Products with superior characteristics can become a source of income for the target community.